COMPARATIVE ANALYSIS OF SHARIA BANK USER PREFERENCES IN TRANSACTIONS IN PTKIN WEST SUMATERA - Hanifah Hanifah; Rusyaida Rusyaida (SEAN Institute, 2023)
The phenomenon that occurs at State Islamic Universities in West Sumatra shows that the number of students at the Faculty of Islamic Business Economics who have Islamic bank accounts is still small with an average rate of 32% when compared to the potential and knowledge possessed by students towards Islamic banking. This type of research is field research using a qualitative approach. The data analysis method uses a descriptive analysis method and the coding uses Nvivo12. The results of the study are that the educational environment significantly influences the preferences of Islamic bank users in transactions, especially towards Islamic bank policies in the campus environment which results in the dominant preference factor for each PTKIN which is different, including: First, UIN Iman Bonjol Padang. campus policies and social factors with a presentation of 53% Islamic bank users. The two UIN Sjech M. Djamil Djambek Bukittinggi factors that most dominantly influence the preference of Islamic bank users are the factor of religiosity and the educational process with a presentation of 22% of Islamic bank users. The three UIN Muhammad Yunus Batusangkar factors that most dominantly influence the preferences of Islamic bank users are the factors of rationality and campus policy with a presentation of 35% of Islamic bank users.